Safety of shorter length of hospital stay for patients undergoing minimalist transcatheter aortic valve replacement. Issue 2 (24th August 2017) - Alkhalil, Ahmad; Lamba, Harveen; Deo, Salil; Bezerra, Hiram G.; Patel, Sandeep M.; Markowitz, Alan; Simon, Daniel I.; Costa, Marco A.; Davis, Angela C.; Attizzani, Guilherme F.
Abstract: Objective: Determine the feasibility and predictors of early discharge after minimalist transcatheter aortic valve replacement (TAVR). Background: Duration of hospitalization has a direct impact on overall cost of care, but the clinical impact of length of stay (LOS) in patients undergoing minimalist TAVR remains unclear. Methods: We studied 268 patients who underwent minimalist TAVR. Short LOS (sLOS) was defined as post‐procedural LOS ≤ 3 days and observed in 163 patients. Prolonged LOS (pLOS) was observed in 105 patients. Propensity score matching based on 39 variables yielded 54 pairs of patients in each group. We analyzed 30‐day mortality, 30‐day re‐hospitalization and long‐term survival data. Multivariate regression models were used to define predictors of sLOS. Results: Thirty‐day mortality was 0% versus 5.5% in the sLOS and pLOS groups, respectively ( P  = 0.08). Incidence of re‐hospitalization was higher in pLOS (13% vs. 3.7%). sLOS was associated with lower odds ratio of minor vascular complication (OR 0.1 [95% CI: 0.01, 0.75], P  = 0.05), any bleeding (OR 0.35 [95% CI: 0.14, 0.87], P  = 0.02), blood transfusion (OR 0.27 [95% CI: 0.08, 0.81], P  = 0.02), and new pacemaker implantation (OR 0.23 [95% CI: 0.1, 0.53], P  < 0.001). Discharge to home had a significantly higher odd ratio for sLOS (OR 8.67 [95% CI: 3.59, 23.11], P  < 0.001). Conclusion: In appropriately selected patients, sLOS following minimalist TAVR approach in an experienced and high volume center is feasible and safe. Implementing such a strategy may reduce medical costs with the potential clinical benefit of early re‐habilitation for the elderly TAVR population.